Causes and Consequences of Wehrlitization Beneath a Trans‐Lithospheric Fault: Evidence From Mesozoic Basalt‐Borne Wehrlite Xenoliths From the Tan‐Lu Fault Belt, North China Craton. Issue 7 (3rd July 2020) - Lin, A‐Bing; Zheng, Jian‐Ping; Aulbach, Sonja; Xiong, Qing; Pan, Shao‐Kui; Gerdes, Axel
Abstract: Trans‐lithospheric faults represent weak zones where some of the most intense interaction between the lithospheric mantle and melts occurs. We carried out detailed petrological observations and mineral chemical analyses of feldspar‐bearing wehrlites entrained in the Mesozoic basalts from Liaoyuan, northeastern North China Craton (NCC) to obtain new insights into the nature and consequences of wehrlitization. Wehrlites ( n = 12) show textural evidence for replacement of orthopyroxene by clinopyroxene, combined with low Ti/Eu (692–4, 425) and variable, though generally high, Ca/Al, (La/Yb)N, and Zr/Hf in clinopyroxenes. This is ascribed to interaction with a silica‐undersaturated, carbonated silicate melt. Feldspar with variable K2 O (0.17–9.84 wt.%) and CaO (0.03–12.8 wt.%) and some clinopyroxene likely formed by decomposition of amphibole and mica during heating prior to entrainment. Integrated with data from peridotite xenoliths in Cenozoic basalts along the Tan‐Lu fault belt (TLFB), these observations indicate deep volatile‐rich melt metasomatism. This may have occurred during a known Late Cretaceous to Early Tertiary extensional stage and was precursory to basaltic magmatism in the north‐south direction along the TLFB. We suggest that wehrlitization beneath the TLFB—and elsewhere—monitors the passage and mobility of carbonated melts linked to lithospheric thinning up to decratonization. Upward transport of the wehrlitizing carbonated melts through the massive TLFB and ultimate degassing of CO2 at the surface during its extensional stage may have contributed to the mid‐Cretaceous greenhouse climate. Key Points: Wehrlitization of mantle lithosphere beneath massive Tan‐Lu fault belt in China is due to interaction with SiO2 ‐undersaturated melts Wehrlitization connected to Mesozoic lithosphere thinning, heating, and basaltic magmatism suggests CO2 mobility in fault belts Feldspar ± clinopyroxene formed by decomposition of phlogopite and amphibole preceding xenolith entrainment